Evolution of grain sizes and orientations during phase transitions in hydrous Mg2SiO4. Issue 10 (30th October 2016) - Rosa, Angelika D.; Hilairet, Nadège; Ghosh, Sujoy; Perrillat, Jean‐Philippe; Garbarino, Gaston; Merkel, Sébastien
Abstract: Transformation microstructures in mantle minerals, such as (Mg, Fe)2 SiO4, are critical for predicting the rheological properties of rocks and the interpretation of seismic observations. We present in situ multigrain X‐ray diffraction experiments on hydrous Mg2 SiO4 at the P / T conditions relevant for deep cold subducting slabs (up to 40 GPa and 850°C) at a low experimental strain rate ( 4 * 10 −6 s −1 ). We monitor the orientations of hundreds of grains and grain size variations during the series of α‐β‐γ (forsterite‐wadsleyite‐ringwoodite) phase transformations. Microtextural results indicate that the β and an intermediate γ* phase grow incoherently relatively to the host α phase consistent with a nucleation and growth model. The β and γ phases exhibit orientation relationships which are in agreement with previous ex situ observations. The β and intermediate γ* show texturing due to moderate differential stress in the sample. Both the α‐β and α‐γ transformation induce significant reductions of the mean sample grain size of up to 90% that starts prior to the appearance of the daughter phase. Apart from the γ *, in the newly formed β and γ phases, the nucleation rate is faster than the growth rate, inhibiting the formation of large grains. These results on grain orientations and grain size reductions in relation to transformation kinetics should allow refining existing slab strength models. Key Points: In situ microstructure tracking with multigrain X‐ray diffraction at high P/T Significant transformational grain size reductions at cold slab conditions No CPO inheritance from α phase. Possible inheritance between β and γ phases